The Relationship between Foreign Direct Investment and Renewable Energy Production: Evidence from Brazil, Russia, India, China, South Africa and Turkey - Kilicarslan, Zerrin (International Journal of Energy Economics and Policy, 2019)
This paper aims to investigate the relationship between foreign direct investment and renewable energy production in BRICS countries and Turkey. For this purpose, the annual data from 1996 to 2015 is examined using with Pedroni co-integration test and panel ARDL test. Test results indicate the existence of long run relationship between renewable energy production and foreign direct investments in BRICS countries and Turkey. Policy makers should adopt appropriate incentive policies to attract foreign direct investments into the renewable energy sector. Keywords: Foreign direct investment, renewable energy production, Panel ARDL method JEL Classifications: F21, Q42, C23 DOI: https://doi.org/10.32479/ijeep.7879